2020
DOI: 10.1039/d0nj00526f
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency improvement in non-enzymatic H2O2 detection induced by the simultaneous synthesis of Au and Ag nanoparticles in an RGO/Au/Fe3O4/Ag nanocomposite

Abstract: Developing a quick and precise technique for hydrogen peroxide (H2O2) detection would open up a new class of technologies for biological, medical and chemical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Due to few studies on MoSe 2 towards the non-enzymatic detection of H 2 O 2 , we hypothesized that the following detection mechanism of the as-proposed biosensor was based on previous research studies. 39,40 The Ag/MoSe 2 -500/ITO can promote the electron transfer from the Ag/MoSe 2 -500 electrode to reduce H 2 O 2 owing to good electronic conductivity.MoSe 2 (Ox) + e − ⇄ MoSe 2 (Red) MoSe 2 (Red) + 2H 2 O 2 ⇄ MoSe 2 (Ox) + 2H 2 O + O 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to few studies on MoSe 2 towards the non-enzymatic detection of H 2 O 2 , we hypothesized that the following detection mechanism of the as-proposed biosensor was based on previous research studies. 39,40 The Ag/MoSe 2 -500/ITO can promote the electron transfer from the Ag/MoSe 2 -500 electrode to reduce H 2 O 2 owing to good electronic conductivity.MoSe 2 (Ox) + e − ⇄ MoSe 2 (Red) MoSe 2 (Red) + 2H 2 O 2 ⇄ MoSe 2 (Ox) + 2H 2 O + O 2 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Fig.3Fshows the DPV of the Ag/ MoSe 2 -500/ITO in N 2 -saturated 0.1 M PBS (pH 7.4) containing different concentrations of H 2 O 2 , and it is obviously observed that the reduction peak current increases with the incremental concentrations of H 2 O 2 . Due to few studies on MoSe 2 towards the non-enzymatic detection of H 2 O 2 , we hypothesized that the following detection mechanism of the as-proposed biosensor was based on previous research studies 39,40. The Ag/MoSe 2 -500/ ITO can promote the electron transfer from the Ag/MoSe 2 -500 electrode to reduce H 2 O 2 owing to good electronic conductivity.…”
mentioning
confidence: 99%
“…It has been proven that electrochemical activity and sensitivity significantly improve with the use of bimetallic NPs [ 202 ]. For example, different combinations of more than one transition metal, such as Au with Ag [ 203 , 204 , 205 ], Co [ 205 , 206 ], Pt [ 201 , 207 , 208 ], Pd [ 209 ], Cu [ 210 , 211 ], Fe 3 O 4 [ 212 , 213 ], or Fe 2 O 3 [ 212 , 213 ], have been intensively investigated and have led to successful development of electrochemical sensors. For instance, Zhao et al [ 204 ] developed Ag-Au bimetallic NPs supported on reduced GO with alginate as a stabilizer and reductant.…”
Section: Hydrogen Peroxide (H 2 O 2 mentioning
confidence: 99%
“…Nanostructured materials are widely used as the working surface of the electrode [ 47 49 ]. The most common are transition metal nanoparticles [ 33 , 37 , 50 54 ], carbon nanotubes [ 8 ], metal oxides [ 55 64 ], graphene [ 32 33 ], and ordered mesoporous carbon [ 38 , 65 66 ]. Compared to bulk materials, nanostructures have higher catalytic activity and a significantly increased surface area-to-volume ratio, which makes it possible to significantly increase both sensitivity of the sensor and rate of detection of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%